Desafios e peculiaridades do PT do Paraná: uma análise da cultura política dos dirigentes petistas - Ayres, Carla Simara Luciana da Silva (2013)
Much has been written about Worker's Party in the literature, which discusses basic and general topics such as the party's foundation, to a more specific ones, such as government experiences and national power achievement. Nevertheless, although Worker's Party is a very well-known subject in political science literature, there are still a few theoretical gaps regarding two main dimensions: cultural and regional; especially when addressed together. Based on that, this study is developed in order to explore one of these gaps, which aims to analyse the political culture of the PT leaders from Paraná state by means of a comparative table, with people responsible to the meetings and conferences. The reason for focusing on Paraná state was the particularities found in terms of party's formation processes, which strongly influence the actions and structure of the party along its agency according to Panebianco. However, it is known that such particularities are due to historical context and economic development of the state which determine the formation of specific groups, and consequently the PT-PR group. As a result, it was found that mobilized sectors in Paraná have different characteristics in comparison to the most recognisable experiences such as those of ABC. In summary, we argue that these different factors tend to influence and create some particularities with regards political culture of these leaders.